2017
DOI: 10.1080/19768354.2017.1284156
|View full text |Cite
|
Sign up to set email alerts
|

From sequencing data to gene functions: co-functional network approaches

Abstract: Advanced high-throughput sequencing technology accumulated massive amount of genomics and transcriptomics data in the public databases. Due to the high technical accessibility, DNA and RNA sequencing have huge potential for the study of gene functions in most species including animals and crops. A proven analytic platform to convert sequencing data to gene functional information is co-functional network. Because all genes exert their functions through interactions with others, network analysis is a legitimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Our results showed that TRRUST v2 not only provides information extracted from the literatures but can also generate novel functional hypotheses to study the transcriptional regulation involved in human diseases. Generation of functional hypothesis using co-functional networks have increased the popularity of such networks, and various network-based algorithms have been developed ( 21 ). Algorithms also need to be developed based on regulatory gene networks to identify key transcriptional regulators associated with human diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that TRRUST v2 not only provides information extracted from the literatures but can also generate novel functional hypotheses to study the transcriptional regulation involved in human diseases. Generation of functional hypothesis using co-functional networks have increased the popularity of such networks, and various network-based algorithms have been developed ( 21 ). Algorithms also need to be developed based on regulatory gene networks to identify key transcriptional regulators associated with human diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have concentrated on direct protein-protein interactions only. Inclusion of other types of interaction has the potential to increase this coverage of the Hymenolepis microstoma somatic proteome; for example, 'regulog' networks link orthologs of regulatory interactions [78] and 'associalog' networks link proteins/genes based on any type of interaction: physical, genetic, regulatory and other types of functional association [50,79,80]. However, these…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of other types of interaction has the potential to increase this coverage of the Hymenolepis microstoma proteome. For example, regulogs networks link orthologs of regulatory interactions [Yu et al, 2004] and associalog networks link proteins/genes based on any type of interaction: physical, genetic, regulatory and other types of functional association [Kim et al, 2013, Lee et al, 2008, Shim et al, 2017]. However, these approaches generally come at the cost of more noise from false positives [Kim et al, 2013, Lee et al, 2008].…”
Section: Discussionmentioning
confidence: 99%